Vaccinia Virus and Poxvirology Methods and Protocols - Isaacs, Stuart N.; Isaacs, Stuart N. (Methods in Molecular Biology,, 2012)
Since the first edition of Vaccinia Virus and Poxvirology: Methods and Protocols was published, a number of important events related to poxvirology have occurred, such as FDA approval of a culture-based live smallpox vaccine and the vaccination of large numbers of U.S. military personnel and relatively large numbers of U.S. civilians. Novel anti-poxvirus therapeutics have been developed and have been used in emergency settings. The second edition of Vaccinia Virus and Poxvirology expands upon the previous edition with entirely new sets of protocols. Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.  Authoritative and practical, Vaccinia Virus and Poxvirology: Methods and Protocols, Second Edition seeks to aid scientists in continuing to study poxviruses using new tools and approaches.